Optimizing of Protease Purification from Bacillus cereus TD5B by Ammonium Sulfate Precipitation - Atik Winarti (Chemical Engineering Transactions, 2018)
The aim of this research was to optimize the protease purification from Bacillus cereus TD5B by ammonium sulfate precipitation. The material used was protease enzyme from Bacillus cereus TD5B. It was produced and purified in a liquid medium using ammonium sulfate precipitation. The optimization was performed using various levels (50, 60, 70 and 80 %) of ammonium sulfate as precipitation agent of crude microbial enzymes. Separation process of precipitate and supernatant was conducted by 3,500 rpm centrifugation for 30 min at 4°C. The specific activity of protease enzyme, and protein content was observed on precipitate and supernatant of each levels treatment of the ammonium sulfate. Based on specific enzyme activity and protein content, the measurement showed that 70 % ammonium sulfate level treatment has the highest specific enzyme activity (78.296 U/mg) and highest protein content (2.689 mg/mL). This specific enzyme activity was three times higher compared to specific enzyme activity before purification treatment (24.12 U/mg). In conclusion, the purification of crude Bacillus cereus TD5B enzyme by ammonium sulfate purification can increase the specific enzyme activity.